Leonardo Sciascia e la funzione sociale degli intellettuali - Francese, Joseph (Studi e saggi, 2012)
Leonardo Sciascia e la funzione sociale degli intellettuali collects the translations of three writings that have already appeared in English-speaking scientific journals - L'onore, il qualunquismo e l'essenzialismo ne L'antimonio di Sciascia, Sciascia e La scomparsa di Majorana and De L'Affaire Moro e della (ri)scrittura della storia - as well as an in-depth introduction that provides an overview of the author's research results on Sciascia - from which a much more conservative Sciascia than is commonly believed is revealed - as well as an analysis of Sciascia's poetics (centred on the public self-image of the "spoiler"). The essay ends with a concluding chapter where the last decade of Sciascia's career is examined (the period after L'Affaire Moro and the participation of the Sicilian writer in the Moro Commission) during which the author publishes various collections of essays - such as La strega e il capitano, 1912+1, Una storia semplice - and traces an essay on Telesio Interlandi, ideologue of the discriminatory legislation of 1938.